“Hot” alkaline hydrolysis of UiO-66 to enhance quercetin loading, in vitro release, antioxidant, and anti-inflammatory properties - Chang, Ruimiao; Wang, Huichun; Liu, Shumian; Jia, Shuai; Wang, Jingjing; Song, Ying; Ji, Xiaolu; Li, Qingqing (Frontiers in Nutrition, 2025)
BackgroundThe Food and Drug Administration (FDA) classifies quercetin (QU) as a generally recognized as safe (GRAS) substance and exhibits striking antioxidant and anti-inflammatory activities. However, its extremely low solubility in water limits its application in the fields of food and nutrition. Nanomaterials such as UiO-66 (University of Oslo 66) have been widely used in the field of nutrient delivery.MethodsIn this study, terephthalic acid ligands were stripped from small-sized UiO-66 via a thermal alkaline hydrolysis method, resulting in a new drug-loaded material, UiO-66-BH-100 (UiO-66 blended and heated, with a size of 100 nm). The obtained UiO-66-BH-100 showed significantly increased porosity and good thermal stability. UiO-66-BH-100, which is rich in hydroxyl groups (1.7 × 1019/m2), could dramatically enhance the adsorption capacity for QU (302.60 vs. 135.57 mg/g). The results of adsorption experiments indicate that the adsorption of QU by UiO-66-BH-100 tends to follow a monolayer adsorption behavior, suggesting that electron pair sharing or transfer may occur during the adsorption process.ResultsThe QU-loaded drug carrier UiO-66-BH-100@QU has good biocompatibility and could significantly improve the in vitro release behavior of QU. Notably, the capacity of UiO-66-BH-100@QU to scavenge diphenyl-2-picrylhydrazyl (DPPH) and 22'-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS), as well as its ability to inhibit NO secretion, was almost comparable to that of QU, demonstrating promising antioxidant and anti-inflammatory potential.ConclusionThis study provides a simple and effective new approach for delivering natural active ingredients with excellent bioavailability in the field of functional foods.